2010
DOI: 10.1158/1541-7786.mcr-09-0445
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast-Derived Matrix Metalloproteinase-9 Directly Affects Angiogenesis in the Prostate Tumor–Bone Microenvironment

Abstract: In human prostate to bone metastases and in a novel rodent model that recapitulates prostate tumor-induced osteolytic and osteogenic responses, we found that osteoclasts are a major source of the proteinase, matrix metalloproteinase (MMP)-9. Because MMPs are important mediators of tumor-host communication, we tested the effect of host-derived MMP-9 on prostate tumor progression in the bone. To this end, immunocompromised mice that were wild-type or null for MMP-9 received transplants of osteolytic/osteogenic-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 40 publications
0
62
0
Order By: Relevance
“…The source of pro-angiogenic MMP-9 might be the tumor cells themselves. Studies from mouse models also suggest bone marrow-derived cells, neutrophils or osteoclasts as potential sources of MMP-9 facilitating tumor angiogenesis (25)(26)(27)(28). We document that the angiogenic properties of conditioned media (CM) from MMP-9 knockdown HCC cells in an LSF-overexpression background were significantly compromised suggesting that MMP-9 plays a key role in the angiogenic function of LSF.…”
Section: Discussionmentioning
confidence: 82%
“…The source of pro-angiogenic MMP-9 might be the tumor cells themselves. Studies from mouse models also suggest bone marrow-derived cells, neutrophils or osteoclasts as potential sources of MMP-9 facilitating tumor angiogenesis (25)(26)(27)(28). We document that the angiogenic properties of conditioned media (CM) from MMP-9 knockdown HCC cells in an LSF-overexpression background were significantly compromised suggesting that MMP-9 plays a key role in the angiogenic function of LSF.…”
Section: Discussionmentioning
confidence: 82%
“…[ [151][152][153] Fibroblasts Fibroblasts produce the support structures, including the bulk of extracellular matrix, for the prostate. In cancer, they may differentiate into a myofibroblast (a cell with characteristics of both fibroblasts and smooth muscle cells).…”
Section: Interleukin-6mentioning
confidence: 99%
“…Again, MMP-9 was implicated in osteoclast migration, invasion and angiogenesis, presumably via an increase in the amount of bioavailable VEGF-A, as the mechanism mediating these effects. Our group has also defined osteoclast derived MMP-9 as mediating angiogenesis in the prostate tumor-bone microenvironment [130]. We observed that in human samples of prostate to bone metastasis, the osteoclasts are a major source of MMP-9 while surprisingly, the human cancer metastases were rarely positive for this MMP.…”
Section: Vegf-amentioning
confidence: 91%
“…In the tumorbone microenvironment, the osteoclast has recently come under scrutiny as a major facilitator of angiogenesis and a number of studies point to MMP-9 being critical for mediating the release of VEGF-A 164 from the bone matrix [21,[130][131][132]. In development, MMP-9 expression by osteoclasts is critical for their invasion into developing long bones, and MMP-9 mediated release of VEGF-A (presumably the VEGF-A 164 isoform) is the principal molecular mechanism underlying this effect [54].…”
Section: Vegf-amentioning
confidence: 99%